Análise da verdade em Foucault - Grazziotin, Bruna Grillo (My University, 2024)
This dissertation intends to elaborate an open and perspective analysis that build the way for possible contributions to the objective of answering the following question: can the truth be an element of agglutination of concepts in Foucault's philosophy? The hypothesis shifts the traditional Foucauldian interpretation - which traditionally takes the power as the guiding line of his thoughts - to the consideration of his concept of truth as a unifying element in his work, with the pondering that power is present in the entire backdrop of Foucault's philosophy. To follow this path, firstly, the relationship between truth and Foucault's philosophical conception of knowledge was approached, followed by the will to know, the will to truth, the subject, and the power. Subsequently, the ramifications of these questions within Foucault's work were pointed, beginning from the archaeological approach to the genealogical perspective, and the subjection of the subjectivity to self-governance, to governability, and to ethics. [resumo fornecido pelo autor]
Esta dissertação pretende elaborar uma análise perspectiva e aberta que constrói caminho para possíveis contribuições para o objetivo de responder à questão: a verdade pode ser um elemento de aglutinação de conceitos na filosofia de Foucault? A hipótese desloca a interpretação foucaultiana - que tradicionalmente toma o poder como fio condutor do seu pensamento - para a consideração do seu entendimento de verdade inserido como elemento unificador de sua obra, com a ponderação de que o poder está presente em todo o pano de fundo da filosofia foucaultiana. Para trilhar esse caminho, primeiramente, foi abordado o vínculo da verdade com a concepção filosófica foucaultiana do conhecimento; da vontade de saber; da vontade da verdade; do sujeito; e, do poder. Após, foram apontados os desdobramentos destas questões na obra foucaultiana, partindo da abordagem arqueológica à genealógica; e, da sujeição da subjetividade ao governo de si, à governamentalidade e à ética. [resumo fornecido pelo autor]
Keywords: Foucault, Michel, 1926-1984; Verdade; Sujeito (Filosofia); Filosofia; Truth; Subject (Philosophy); Philosophy